Long‐term progression of white matter hyperintensities in ischemic stroke. (24th September 2018) - Holmegaard, Lukas; Jensen, Christer; Redfors, Petra; Blomstrand, Christian; Jern, Christina; Jood, Katarina
Abstract : Objectives: Studies on long‐term progression of white matter hyperintensities (WMH) after ischemic stroke are scarce. Here, we sought to investigate this progression and its predictors in a cohort presenting with ischemic stroke before 70 years of age. Materials and methods: Participants in the Sahlgrenska Academy Study on Ischemic Stroke who underwent magnetic resonance imaging (MRI) of the brain at index stroke were examined by MRI again after 7 years (n = 188, mean age 53 years at index stroke, 35% females). WMH at index stroke and progression were assessed according to Fazekas' grades and the WMH change scale. Stroke subtype was classified according to TOAST. Results: Marked WMH at index stroke were present in 20% of the participants and were significantly associated with age, hypertension, and subtype. Progression of WMH after 7 years was observed in 63% and 35% of the participants for subcortical and periventricular locations, respectively. Significant independent predictors of progression were age and marked WMH at baseline for both locations, whereas no significant associations were detected for vascular risk factors or subtype in multivariable analyses. In participants with no or only mild WMH at baseline, 20% showed marked WMH at follow‐up. Age and hypertension, but not subtype, were independently associated with this acquisition of marked WMH. Conclusions: Age and marked WMH at index stroke, but not stroke subtype, predicted long‐term WMH progression after ischemic stroke before 70 years of age, whereas age and hypertension predicted acquisition of marked WMH in those with no or only mild WMH at baseline.